2015
DOI: 10.3945/jn.114.200238
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene and Apo-10′-lycopenoic Acid Have Differential Mechanisms of Protection against Hepatic Steatosis in β-Carotene-9′,10′-oxygenase Knockout Male Mice

Abstract: Our data suggest that lycopene and APO10LA inhibit HSFD-induced steatosis in BCO2-KO male mice through differential mechanisms. Sex disparity of BCO2-KO mice was observed in the outcomes of HSFD-induced liver steatosis and plasma lipids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 64 publications
(103 reference statements)
4
41
0
Order By: Relevance
“…Our results showed that supplementation with lycopene or TP for 12 weeks ameliorated the hepatic steatosis induced by HFD, which is consistent with several studies that demonstrated the amelioration of hepatosteatosis under lycopene or tomato products effect . The protective effects of lycopene and TP in hepatosteatosis may be related to multiple mechanisms , including anti‐oxidant/anti‐inflammatory effects and lipid metabolism modulation . In agreement, we reported an anti‐inflammatory effect of lycopene or TP in the liver but also an impact on lipid metabolism.…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed that supplementation with lycopene or TP for 12 weeks ameliorated the hepatic steatosis induced by HFD, which is consistent with several studies that demonstrated the amelioration of hepatosteatosis under lycopene or tomato products effect . The protective effects of lycopene and TP in hepatosteatosis may be related to multiple mechanisms , including anti‐oxidant/anti‐inflammatory effects and lipid metabolism modulation . In agreement, we reported an anti‐inflammatory effect of lycopene or TP in the liver but also an impact on lipid metabolism.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, this pattern suggests that lycopene cleavage metabolites produced by BCO2 may have anti-prostate-cancer bioactivity and that their production is diminished in the Bco2−/− mice. Previous studies on the effect of the lycopene metabolite, apo-10’-lycopenoic acid, have shown it to reduce hepatic inflammation, steatosis, and tumorigenesis in mice (60, 61), and other studies of apo-8’-lycopenal in models of liver cancer have been indicative of bioactivity (38, 39), increasing the plausibility of lycopene metabolite activity in the prostate. We also demonstrate that tomato-fed Bco2−/− accumulate lycopene precursors, phytofluene, zeta-carotene, and a suggestion for phytoene, opening the door for hypotheses regarding the potential for BCO2 to cleave additional carotenoids.…”
Section: Discussionmentioning
confidence: 99%
“…Martín-Pozuelo et al [24] described a decrease in urinary isoprostranes and an over-expression of genes related to mitochondrial and peroxisomal fatty acid oxidation in rats with steatosis that had drunk tomato juice (HL group). In general, other authors, using different experimental designs, have reported a beneficial effect of tomato or lycopene consumption on NAFLD, by reduction of the oxidative stress and also improvement of the lipid metabolism, exerting a preventive effect on the progression to NASH [22,23,25]. …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, lycopene has been found to be a most effective antioxidant for liver health [20], showing different beneficial effects on liver metabolism in rats with induced NAFLD. Related to this, different authors have described, in animal models, a preventive effect of tomato consumption on steatosis, increasing mitochondrial and peroxisomal fatty acid oxidation [21,22,23,24], that could prevent the development of NASH due to the inhibitory effect of lipid peroxidation in the liver tissue [25,26]. …”
Section: Introductionmentioning
confidence: 99%